PENGARUH KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Ihdina Syafitri; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study uses secondary data from 10 sampled the financial statements of property and real estate companies and sampling using purposive sampling techniques. Analysis of data using the multiple linear regression analysis, t-test, f, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 20.The results showed that the variables financing decision and dividend policy partially (t test) significantly affects the firm value on the property and real estate companies in the Indonesia Stock Exchange (BEI). The results of the study simultaneously (f test) showed a significant effect of the variable financing decision and dividen policy to firm value in property and real estate companies listed in the Indonesia Stock Exchange (BEI).Keywords: financing decisions, dividend policy, the firm Value